Hormonal relationship in the chronic development of schizophrenia spectrum and other psychotic disorders in adolescent patients: Literature update - Macias Paz, Ignacio Uriel; Calles Vicencio, Ana Carla; Ávila Silva, Anette Michelle; Ramos Gómez, Christian Jair; Ledesma Compean, Victoria Alexa; Guerra Cárdenas, José Eugenio (Medicina e Investigación Universidad Autónoma del Estado de México; Vol. 12 Núm. 1 (2024): Revista de Medicina e Investigación Universidad Autónoma del Estado de México, 2024)
Abstract Adolescence is established as an important stage in the human being, we try to show how positive or negative this stage can be in the development of an adequate environment, elucidating the benefits or consequences that can affect the psychomotor development of a person. Adolescence is the time when the personality of an individual is defined, influenced by various factors that can help the subject to develop adequately in society, as well as factors that can affect the subject conditioning him/her to an environment that is not favorable for his/her development. Both physical and psychological changes are mentioned, as well as hormonal factors which play an important role in development. It is intended to demonstrate the hormonal mechanisms that condition the changes in the development of the human being.     TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian   //   TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE setTimeout(function(){var s=document.createElement('script');s.type='text/javascript';s.charset='UTF-8';s.src=((location && location.href && location.href.indexOf('https') == 0)?'https://ssl.microsofttranslator.com':'http://www.microsofttranslator.com')+'/ajax/v3/WidgetV3.ashx?siteData=ueOIGRSKkd965FeEGM5JtQ**&ctf=true&ui=true&settings=manual&from=en';var p=document.getElementsByTagName('head')[0]||document.documentElement;p.insertBefore(s,p.firstChild); },0); "> Enable collaborative features and customize widget: Bing Webmaster Portal Back // ORIGINAL: "; langMenu.appendChild(origLangDiv); LanguageMenu.Init('LanguageMenu', LanguageMenu_keys, LanguageMenu_values, LanguageMenu_callback, LanguageMenu_popupid); window["LanguageMenu"] = LanguageMenu; clearInterval(intervalId); } }, 1); // ]]>